Synthesis of tricyanovinyl-substituted thienylpyrroles and characterization of the solvatochromic, electrochemical and non-linear optical properties - Raposo, M. Manuela M. (2005)
Tricyanovinyl-substituted 1-(alkyl)aryl-2-(2´-thienyl)pyrroles 1 have been synthesized by direct tricyanovinylation reaction of 1-(alkyl)aryl-2-(2´-thienyl)pyrroles 2 using TCNE. The tricyanovinyl- derivatives 1 display dramatic reductions in both their optical and electrochemical band gaps relative to thienylpyrrole precursors 2. The solvatochromic behavior of compounds 1 was investigated in a variety of solvents. Hyper-Rayleigh scattering was used to measure the first hyperpolarizabilities β of the mentioned compounds. The β values show that the new compounds prepared could be used on the manufacture of materials with good non-linear (NLO) properties.